An examination on the ageing performance of palm oil and coconut oil with consideration on the presence of insulation paper - Mohamad, Nur Aqilah (2016)
Mineral Oil (MO) has been a major type of dielectric insulation fluid in transformers. However, due to the increasing tight regulations on safety and environment in recent years, a number of studies have been carried out to explore an alternative fluid for MO. Palm Oil (PO) and Coconut Oil (CO) have been introduced as a suitable candidate for transformers application. Before these oils can be applied in-service, several assessments such as ageing performance need to be carried out at laboratory level in order to determine the feasibility of these oils for practical application. There are two sets of laboratory accelerated ageing experiments were carried out. The first part involved are the ageing of oil at 85 ºC and 115 ºC under open condition. The second part examined the ageing of oil with the presence of insulation paper and high moisture content at 90 ºC, 110 ºC and 130 ºC. The properties of three different variations of RBDPO and one sample of CO were measured and analysed through AC breakdown voltage, dielectric properties, physicochemical properties and tensile strength of paper. Finally, the degradation rates of paper aged in RBDPO and CO were analysed based on the Weidmann model. Only resistivity of RBDPO and dielectric dissipation factor of CO show a clear reduction trends throughout the ageing duration while other electrical properties of these oils remain almost unaffected by the ageing under open condition. The effect of oxidation is not apparent on RBDPO and CO since the viscosities remain almost unchanged and the acidities remain low throughout the ageing duration. There are no clear trends of moisture that can be observed for both RBDPO and CO. Under sealed condition, the AC breakdown voltages and relative permittivities of RBDPO, CO and MO are not significantly affected by the ageing. There is no significant changes on the resistivities of CO and MO while for RBDPO, it decrease as the ageing progresses. Only the dielectric dissipation factor of CO shows a clear reduction trend. The acidities of RBDPO and CO remain at low level and within the range of MO. The moistures in RBDPO and CO reduce as the ageing progresses. The trends of moisture in paper for RBDPO and CO at different temperatures are the same as MO. With no significant on most of the electrical properties, RBDPO and CO have a bright opportunity to be applied either in free breathing or hermetically sealed transformers. The reductions of Tensile Index (TI) of RBDPO and CO are not severe in MO and maintain at value higher than 50% retention of TI. Based on Weidmann model, the ageing rate of paper aged in RBDPO and CO could be 2.02 lower than MO. This property is one of the encouraging outcomes for RBDPO and CO especially on extending the operation life of transformers. An advantage is gain where the effect of oxidation on the RBDPO and CO can be minimized